A study on iron and chemical oxygen demand (COD) removal by heat treated zeolite media - Ragunathan, Santiagoo; Naimah, Ibrahim; Azlinda, Abdul Ghani; Nurhawani, Halim (Universiti Kuala Lumpur (UniKL), 2008)
Organized by Universiti Kuala Lumpur (UniKL), 11th - 13th December 2007 at Renaissance Hotel, Kuala Lumpur.